2006
DOI: 10.1507/endocrj.53.255
|View full text |Cite
|
Sign up to set email alerts
|

Acute Onset of Steroid Psychosis with Very Low Dose of Prednisolone in Sheehan's Syndrome

Abstract: Abstract. Corticosteroid treatment is frequently associated with psychiatric disturbances. These adverse effects are unusual with low dose of corticosteroid. We describe a patient who rapidly developed a steroid-induced psychosis with very low dose of prednisolone. A 48-year-old woman of Sheehan's syndrome was admitted to hospital with insomnia, euphoric moods and visual hallucinations. She had taken prednisolone (10 mg in the morning and 5 mg at night) for 6 days before admission. These symptoms appeared afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 14 publications
1
18
2
Order By: Relevance
“…However, even for this group there were problems associated with the unpleasant emotional state, mood swings, and temperamental behaviors. As noted elsewhere (Hong et al, 2006;Patten & Neutel, 2000), euphoria, mood disorders, and even mania can be associated with steroid use.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…However, even for this group there were problems associated with the unpleasant emotional state, mood swings, and temperamental behaviors. As noted elsewhere (Hong et al, 2006;Patten & Neutel, 2000), euphoria, mood disorders, and even mania can be associated with steroid use.…”
Section: Discussionmentioning
confidence: 65%
“…In the current study, the participant who reported experiencing psychosis from steroids remained in this state for many months while on treatment and required ongoing psychiatric care. Although documented as uncommon, psychosis is noted as a complication of steroids in a number of diagnostic conditions other than hematological malignancies such as myocardial infarction, asthma, and Sheehan's syndrome (Alisky, 2006;Hong et al, 2006;Koh et al, 2002). Depression has been reported elsewhere as a serious side effect of steroid administration in a case study of a 15-year-old girl with acute lymphoblastic leukemia, a common hematological malignancy (Sutor et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Typical sequelae from the use of corticosteroids can include symptoms such as insomnia, euphoric moods, mood disorders (with depressive, manic and mixed features), mania and visual hallucinations [12,14,25,27], severe depression [13], irritability, violence [1], neuropsychological deficits and psychotic states [15,25,32].…”
Section: Introductionmentioning
confidence: 99%
“…Withdrawal of prednisolone was associated with improvement but reintroduction of small dose of 2.5 mg again resulted in agitation. After stopping prednisolone and starting a low dose of hydrocortisone (10mg) followed by gradually building up the dose did not result in recurrence of psychotic symptoms (7). In our first patient we stopped prednisolone for five days and introduced 5 mg of hydrocortisone daily.…”
Section: Discussionmentioning
confidence: 79%